HUBUNGAN ASESMEN DENGAN TUJUAN PEMBELAJARAN IPA PADA SISWA SDN 80/I MUARA BULIAN - Annisa Humaila; Zhafira Sayyidatunnisa; Oliver Chelsea Sitanggang; Ayatullah Muhammadin Al Fath; Erwin Efendi Hutagalung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between assessment and science learning objectives at SDN 80/1 Muara Bulian. This research employed a qualitative approach with a case study design. The subjects of this study were teachers and students involved in science learning activities. Data were collected through observation, interviews, and documentation. The data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results showed that learning objectives had been developed based on existing teaching documents; however, they were still general and not fully elaborated into specific and measurable indicators. The implementation of assessment in science learning was dominated by written tests focusing on cognitive aspects. Meanwhile, learning objectives emphasizing science process skills were not fully supported by appropriate forms of assessment. In addition, several constraints were identified, including limited time, large class sizes, and limited ability to design varied assessment instruments. In conclusion, the relationship between assessment and learning objectives exists but is not yet fully aligned. Therefore, efforts are needed to improve alignment through more specific formulation of learning objectives and the development of more varied and authentic assessment practices.